Sharia Finance Inclusion and Poverty Reduction In Palopo City: The Mediation Role of Small and Medium Micro Enterprises - Hamida Hamida; Erwin Erwin; Muhammad Nur Alam Muhajir; Nur Ariani Aqidah; Muh Andi Almahdy (Hasanuddin Economics and Business Review, 2026)
This study examines the effect of Islamic financial inclusion on poverty alleviation in Palopo City, Indonesia, with specific attention to the mediating role of Micro, Small, and Medium Enterprises (MSMEs). It addresses whether access to Sharia-compliant financial services can generate inclusive economic outcomes through MSME development in a secondary city context. A quantitative approach was used by surveying 100 MSME owners who utilize Islamic financial services in Palopo City. Respondents were selected through purposive sampling based on MSME registration, business experience, and use of Sharia financial products. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships among Islamic financial inclusion, MSME performance, and poverty alleviation. The results show that Islamic financial inclusion has a positive and significant effect on poverty alleviation and MSME performance. However, MSME performance does not significantly affect poverty alleviation and does not mediate the relationship between Islamic financial inclusion and poverty alleviation. This indicates that Islamic financial inclusion may improve welfare directly, but MSME growth alone is insufficient to translate financial access into poverty reduction. This study contributes to Islamic finance and development economics by challenging the assumption that financial inclusion automatically reduces poverty through MSME performance. Focusing on Palopo City, it provides micro-level evidence that Sharia financial inclusion requires complementary business capacity, market access, and institutional support to become an effective poverty alleviation strategy.